2017
DOI: 10.3390/su9122264
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Value of Housing Schemes through Sustainable Return on Investment: A Path towards Sustainability-Led Evaluations?

Abstract: The 2016 United Nations (UN) New Urban Agenda clearly reaffirms the concept that sustainable cities require intertwined environmental and social sustainability. The United Nations Sustainable Development Goal (SDG) 11—“Make cities inclusive, safe, resilient, and sustainable”—sets (as a primary target) the provision of sufficient affordable housing. Despite the central role that housing plays in ensuring sustainability and the importance of both environmental and social pillars in ensuring sustainable developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…", look closely at the link between environmental and social sustainability in urban spaces. From this perspective they look at the issue of housing in cities [7]. To this end, they demonstrate how sustainable return on investment can successfully describe and analyze a range of externalities, related to the sustainable value generated by social housing regeneration schemes.…”
Section: How To Address Challenges To Wellbeing and Quality Of Life Imentioning
confidence: 99%
“…", look closely at the link between environmental and social sustainability in urban spaces. From this perspective they look at the issue of housing in cities [7]. To this end, they demonstrate how sustainable return on investment can successfully describe and analyze a range of externalities, related to the sustainable value generated by social housing regeneration schemes.…”
Section: How To Address Challenges To Wellbeing and Quality Of Life Imentioning
confidence: 99%
“…This new research provides insights to 'macro-level drivers, material flows and large Infrastructure developments', which they contend is the critical requirement of research because 'major nexus challenges are faced at local level'. Dean et al (2017) considered the definition of project success is currently too narrow and concluded that the inclusion of socio-economic assessments, as well as environmental, were needed to derive improved investment decisions, exclaiming that "current evaluative methods that support decision making on social housing interventions fail to capture all of the socio-environmental value contained in the UN SDG 11". Their study addressed the issue by demonstrating how Sustainable Return on Investment can successfully describe and analyse a range of externalities related to the sustainable value generated by social housing regeneration schemes. This view was complemented by Schwanitz et al (2017) and Diaz-Sarachaga et al (2016) where both research teams analysed the fundamental basis for investment decisions.…”
Section: Sdg-ip Future Research Issue 1 Cascading From Global To the Local Levelmentioning
confidence: 99%
“…How does the theory of a temporary organisation effect the measurement of SDGs at project level as compared to the organisational level? Dean et al, 2017;Diaz-Sarachaga et al, 2016;Schwanitz et al, 2017;da Silva et al, 2019 Does the current definition of project success place sufficient value in the wider criteria across environmental and societal factors as well as existing economic drivers?…”
Section: Sdg-ip Future Research Issue 3 Sustainable Constructionmentioning
confidence: 99%